Hot Embossing of Micro Grating and Its Replication Accuracy - Muhammad Syahrir, Ahmad; Ahmad Rosli, Abdul Manaf (Semarak Ilmu Publishing, 2024)
The Hot Embossing (HE) process was applied in the fabrication of micro grating. High-density polyethene (HDPE) was used as a specimen material for producing microstructure components and parts. In this research, a series of experiments were conducted using an HDPE specimen and embossed the polymer under different parameters such as temperature, embossing time, and embossing force as factors. The experimental setup was based on a response surface method (RSM) that employed a face composite design. The constructed RSM quadratic models assisted in analysing the response parameters, namely accuracy and surface roughness, to determine the relevant linkages between the input variables and the replies. The results defined that hot embossing temperature and hot embossing force will enhance the accuracy and surface quality of the micro grating. Based on RSM, the results revealed that the optimal parameters were as follows: hot embossing temperature is 1650c, embossing force is 10kN/s, and embossing holding time is 150 seconds. Under this condition, the actual deviation of accuracy and surface roughness is 5,75% and -1.32% respectively compared to the actual size of the micro grating mould. Hence, it is highly agreed with the model prediction value. In conclusion, optimization of process parameters on the hot embossing system that was developed is promising to fabricate the HDPE micro grating substrate with optimum dimensional accuracy and surface quality.